Phenomenological Inflationary Model in Supersymmetric Quantum Cosmology - Nephtalí E. Martínez-Pérez; Cupatitzio Ramírez-Romero; Víctor M. Vázquez-Báez (Universe, 2022)
We consider the effective evolution of a phenomenological model from FLRW supersymmetric quantum cosmology with a scalar field. The scalar field acts as a clock and inflaton. We examine a family of simple superpotentials that produce an inflation whose virtual effect on inhomogeneous fluctuations shows very good agreement with PLANCK observational evidence for the tensor-to-scalar ratio and the scalar spectral index.